2020
DOI: 10.1177/0963689720916173
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of sh-miR-199a-5p-Modified Olfactory Ensheathing Cells Promotes the Functional Recovery in Rats with Contusive Spinal Cord Injury

Abstract: MicroRNAs (miRNAs) function as gene expression switches, and participate in diverse pathophysiological processes of spinal cord injury (SCI). Olfactory ensheathing cells (OECs) can alleviate pathological injury and facilitate functional recovery after SCI. However, the mechanisms by which OECs restore function are not well understood. This study aims to determine whether silencing miR-199a-5p would enhance the beneficial effects of the OECs. In this study, we measured miR-199a-5p levels in rat spinal cords wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…These finding are consistent with presumed structural changes following successful treatment such as restoring axonal integrity and remyelination. Similar findings of increased FA after treatment were recently reported by Gao et al (2020). Interestingly, based on the provided SNR data by Ellingson et al (2008a), we managed to obtain comparable image quality using ex vivo DTI in magnetic field far below preclinical 9.4 T standard as was proposed by de Graff et al (2006).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These finding are consistent with presumed structural changes following successful treatment such as restoring axonal integrity and remyelination. Similar findings of increased FA after treatment were recently reported by Gao et al (2020). Interestingly, based on the provided SNR data by Ellingson et al (2008a), we managed to obtain comparable image quality using ex vivo DTI in magnetic field far below preclinical 9.4 T standard as was proposed by de Graff et al (2006).…”
Section: Discussionsupporting
confidence: 85%
“…3). The same approach was used by Gao et al (2020) to present only a visual qualitative parameter of applied treatment. However, tractography can provide additional set of parameters with respect to fiber length and fiber number together with tract-based ROI selection with following DTI metrics evaluation.…”
Section: Tractographymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the drastically changing inflammatory environment during this period could affect cell survival and differentiation, which impairs therapeutic effects and causes experimental biases. To avoid controversy, our previous study showed an adequate survival rate of OECs transfected with GFP lentivirus at 7 days after transplantation [43]. Transcriptional upregulation of Cxcl9 and Nos2 was found after OECs transplantation, implying that acute OECs injection might trigger immune rejection against foreign graft cells in the spinal cord [39].…”
Section: Discussionmentioning
confidence: 99%
“…Bao et al illustrated that miR-199a-5p could defend the spinal cord against ischemia/reperfusion-mediated injury through inhibiting ECE1 expression in rats [ 136 ]. However, Gao et al revealed that decreased miR-199a protected against neuronal damage and contributed to functional recovery through upregulation of SIRT1, deacetylation of p53 and the activation of mammalian-target-of-rapamycin signaling pathway in Spinal Cord Injury of rats [ 137 139 ]. Inhibition of miR-199a could encourage neuroprotection through upregulating Sirtl expression in the brain ischemic tolerance of rats [ 140 ].…”
Section: Mirna Alterations Associated With Pnimentioning
confidence: 99%